2006
DOI: 10.1111/j.1423-0410.2006.00754.x
|View full text |Cite
|
Sign up to set email alerts
|

No evidence of West Nile virus infection in Dutch blood donors

Abstract: No evidence of the presence of WNV RNA in Dutch blood donor samples from 2004 was found. However, surveillance of this emerging infection is of importance to safeguard the blood supply in the future because the transmission cycle of WNV is complex and hard to predict.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
1
5
0
1
Order By: Relevance
“…This outcome is in accordance with the recent WNV-RNA screening results of more than 60,000 Dutch blood donors [Koppelman et al, 2006]. Regardless, blood donors who had just recently visited a WNV endemic country (e.g., the USA) are excluded from the actual donation as a precautionary measure in German blood banks.…”
Section: Wnv-rna Incidencesupporting
confidence: 52%
“…This outcome is in accordance with the recent WNV-RNA screening results of more than 60,000 Dutch blood donors [Koppelman et al, 2006]. Regardless, blood donors who had just recently visited a WNV endemic country (e.g., the USA) are excluded from the actual donation as a precautionary measure in German blood banks.…”
Section: Wnv-rna Incidencesupporting
confidence: 52%
“…Evidence of WNV circulation among birds has been reported in the UK since 2003, and in 2006 the use of sentinel chickens corroborated the epidemiological data about WNV in the UK by demonstrating actual seroconversion [18,19]. As far as the remaining European countries are concerned, reports indicated that blood donors were seronegative for WNV in Tyrol, Austria [20] and in The Netherlands [21], whereas the prevalence of anti-WNV neutralizing antibodies was very low (0.03%) among blood donors in Germany. Nevertheless, a recent evaluation of immunoglobulin preparations produced from human plasma collected in Austria, Germany and the Czech Republic indicated increasing WNV antibody titres in preparations from 2009 and 2010, suggesting past WNV exposure of just under 1% of the population of these three central European countries [22].…”
Section: Epidemiology Of Wnv In Eu Member Countries and Neighbouring mentioning
confidence: 89%
“…The relatively high initial reactive rate of blood samples (0.24%) and invalid rate (0.9%) has not been a serious concern, as comparable results have also been reported in similar studies conducted in Mexico (Sánchez‐Guerero et al ., 2006) and the Netherlands (Koppelman et al ., 2006), respectively. In our opinion, in countries with low prevalence of WNV such as Greece, initial reactive blood donations detected by PCR assays should not be excluded from blood supply unless their reactivity is replicated by the same or another method.…”
Section: Discussionmentioning
confidence: 99%